Plasticity of trait divergence in threespine stickleback (Gasterosteus aculeatus) from Lake Mývatn, Iceland - Delarue, Coralie, 1989- (2017)
Lake Mývatn is one of the best-studied ecosystems in Iceland showing strong environmental gradients (e.g. in temperature, substrate) and spatial and temporal differences in invertebrate composition. Many invertebrates groups are found in the lake, in particular chironomid midges and benthic cladocerans that are important prey for threespine stickleback (Gasterosteus aculeatus). As adaptive divergence in response to natural selection is frequently related to diet and/or habitat use, the spatial and temporal variation in prey type and abundance in lake Mývatn may facilitate resource-mediated diversification of stickleback. Along this line, lake Mývatn stickleback show phenotypic differences in i) feeding morphology and ii) body size, likely mediated by responses to prey and temperature. However, it is not know to date whether these phenotypic differences are due to genetic or plastic responses. I performed a laboratory common garden rearing experiment to test for the relative contribution of plastic and genetic effects on key phenotypic traits in stickleback from two habitats in the lake (Mined and Warm). Full-sib offspring from artificial crosses were raised at a combination of two different diets (“benthic midge” vs. “pelagic pellet”) and temperatures (13 and 23°C) up to nine months. I found consistent differences between the two habitat types in gill raker number, body size and age at sexual maturation, but also strong plastic responses in body size, gill raker morphology, body shape, head shape and genotype x environment interactions. My results highlight the importance of considering the complementary effects of selection, phenotypic plasticity and gene flow in order to assess adaptive divergence in natural systems Í Mývatni, sem er eitt mest rannsakaða vistkerfi á Íslandi, má sjá sterka stigla í umhverfisþáttum (t.d. hita, dýpi og botngerð), sem og mikinn breytileika í tíma og rúmi. Í vatninu má finna fjölmarga hópa smádýra, sérstaklega ber að nefna mýlirfur og botnlægar krabbaflær sem eru mikilvæg fæða ...